Energy balance, efficiency and operational limits of the dynamo type flux pump. (1st June 2022) - Morandi, A; Russo, G; Fabbri, M; Soldati, L
Abstract: In rotating flux pumps, a rectified voltage, with non-zero DC component, is obtained at the terminals due to the combined effect of the distributed AC electromotive force, produced by one or more permanent magnets in circular motion and the non-linear resistivity of the superconductor. Overcritical currents are continuously induced in the tape during operation, giving rise to the DC voltage and producing, at the same time, dissipation. In this paper, the energy behavior of the flux pump is numerically investigated. It is shown that induced currents interact with the rotating magnet(s), producing a resistant torque that is little affected by the output current of the flux pump. Due to this interaction mechanism, a significant part of the mechanical power supplied to the rotor is converted into Joule heating within the tape. The paper also explores the operational limits of the flux pump, showing that the generator operation, involving an electric power delivered to the load combined with a mechanical power supplied to the rotor, can only be achieved in a restricted range of current and voltage at the terminals and that the maximum power transfer and efficiency are reached at the middle of the generator range. Under no conditions, the mechanical torque produced on the rotor can be reversed, reaching the motor mode involving an electric power absorbed at the terminals combined with a mechanical power produced on the rotor. A revised equivalent circuit comprising, besides the effective resistance reported in the literature, a further intrinsic resistance is proposed in the paper for taking all the dissipation mechanisms into account. It is shown that this equivalent circuit can predict the energization of an RL load both concerning the final steady values and the full time-domain behavior of the current (including ripples).